Retention of Physical Gains in the Community Following Physical Training for Multiple Sclerosis: A Systematic Review and Implications - Mark, Victor W. (Seminars in Neurology, 2021)
Multiple sclerosis (MS) is a progressive neurological illness whose typically young adult onset results in a nearly entire lifetime of worsening disability. But despite being an unrelenting neurodegenerative disease, numerous clinical trials over the past 40 years for MS have vigorously attempted to improve or at least stabilize declining physical function. Although the vast majority of the studies assessed training effects only within controlled laboratory or clinic settings, in recent years a growing interest has emerged to test whether newer therapies can instead benefit real-life activities in the community. Nonetheless, comparatively little attention has been paid to whether the training gains can be retained for meaningful periods. This review discusses the comparative success of various physical training methods to benefit within-community activities in MS, and whether the gains can be retained long afterward. This review will suggest future research directions toward establishing efficacious treatments that can allow persons with MS to reclaim their physical abilities and maximize functionality for meaningful periods.
Keywords: multiple sclerosis; rehabilitation; recovery; assessment; physical therapy